Plasma synthesis of defect-rich flexible carbon cloth decorated with PtRu alloyed nanoclusters for highly efficient pH-universal electrocatalytic hydrogen evolution. Issue 42 (21st October 2022) - Zhang, Jingsen; Zhang, Xiuling; Shi, Chuan; Xia, Guangqing; Li, Hong; Wang, Peng; Di, Lanbo
Abstract : Defect-rich flexible carbon cloth decorated with ultralow-loading (0.1 wt%) PtRu alloyed nanoclusters (PtRu/CC-P) was synthesized using cold plasma. The PtRu/CC-P exhibited superior activity and stability to Pt/C for the highly efficient pH-universal HER. Abstract : Designing electrocatalysts with superior activity and stability to Pt/C for the highly efficient pH-universal electrochemical hydrogen evolution reaction (HER) still remains an urgent challenge. Herein, we report a facile plasma method for the preparation of defect-rich flexible carbon cloth decorated with ultralow-loading (0.1 wt%) PtRu alloyed nanoclusters (PtRu/CC-P) to resolve these problems. Remarkably, the developed PtRu/CC-P catalyst delivered a high mass activity of 3.77 A mg −1 ( η = 100 mV), almost 3.6 times higher than that of the benchmark HER electrocatalyst 20%Pt/C (1.05 A mg −1 ). Meanwhile, it only required a low overpotential of 44 mV to achieve a current density of 10 mA cm −2 in alkaline media. Systematic experimental and DFT calculation results revealed that the Pt–Ru bridge of PtRu alloyed nanoclusters in PtRu/CC-P can optimize the adsorption strength of HER intermediates at active sites, decrease the H2 O dissociation energy barrier, and consequently facilitate the HER kinetics. Inspiringly, when the PtRu content was increased to 1 wt%, PtRu/CC-P still exhibited a relatively low overpotential of 276 mV even at a high current density of 1000 mA cm −2 and maintained excellent durability at a relatively high current density of 50–500 mA cm −2 for more than 15 h in alkaline media. In addition, PtRu/CC-P also showed brilliant HER activity and stability in neutral and acidic media. This facile method provides a feasible route for the rational design of Pt-based alloyed catalysts toward industrial hydrogen production at all-pH values.